A survey on machine learning techniques for fraud detection in healthcare - S.K, Shamitha; Ilango, V. (International Journal of Engineering and Technology, 2019)
An exponential upward change in fraud occurrence has resulted in billions of dollars loss in the world economy. Newer techniques in fraud detection in healthcare domain are continuously evolving and are put into practice in many business fields. In healthcare Fraud detection, user behavior is monitored to analyze and find any suspicious or undesirable behavior and to avoid the same. Undesirable behavior could be anything like crime, fraud, unwarranted intrusion or any other kind of default. The goal of this paper is to provide a comprehensive review of different types of fraud and fraud detection techniques used in last two decades.Â Â